Factors associated with early dropout in an employer‐based commercial weight‐loss program - E. Alexander; E. Tseng; N. Durkin; G. J. Jerome; A. Dalcin; L. J. Appel; J. M. Clark; K. A. Gudzune (Wiley, 2018)
Summary Objective Minimizing program dropout is essential for weight‐loss success, but factors that influence dropout among commercial programs are unclear. This study's objective was to determine factors associated with early dropout in a commercial weight‐loss program. Methods A retrospective analysis of a remotely delivered, employer‐based commercial program from 2013 to 2016 was conducted. The dependent variable was 'early dropout', defined as enrollees who disengaged from telephone coaching by month 2's end. Independent variables included demographics, program website engagement and early weight change. Multivariate logistic regression analyses were used to assess for differences in early dropout by several factors, adjusted for employer clustering. Results Of the 5,274 participants, 26.8% dropped out early. Having ≥1 chronic condition (odds ratio [OR] 1.41, p < 0.001) and 'weight‐loss failure' defined as ≥0% weight change at month 1's end (OR 1.86, p < 0.001) had significantly increased odds of early dropout. Increasing age by 10‐year intervals (OR 0.90, p = 0.002) and 'meeting the website login goal' defined as ≥90 logins in 3 months (OR 0.13, p < 0.001) significantly decreased the odds of early dropout. Conclusions Presence of comorbidities, less online engagement and weight‐loss failure were associated with early dropout in a commercial program. Strategies to prevent dropout among high‐risk participants, such as increased support or program tailoring, should be developed and tested.